2005
DOI: 10.1161/01.cir.0000161956.75255.7b
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Body Mass Index and Framingham Risk Score in Predicting Incident Coronary Disease in Families

Abstract: Background-Siblings of individuals with premature coronary heart disease (CHD) have a marked excess risk of CHD risk factors and premature CHD. The impact of body mass index (BMI) on incident CHD in these families and the extent to which it may be mediated by associated risk factors are unknown. The aim of this study was to examine the effect of high BMI on incident CHD in white and black families with premature CHD and to estimate the heritability of BMI. Methods and Results-Risk factors, BMI, and Framingham … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 49 publications
2
33
0
4
Order By: Relevance
“…It has been reported that obesity is involved in the onset of CAD 27,28 and in the present study BMI was found to be significantly higher in the recurrence group, which is consistent with the recently proposed concept of metabolic syndrome in which abdominal obesity is an important risk factor for cardiovascular disease.…”
Section: Relationships Between Risk Factors and Recurrence Of Ischemisupporting
confidence: 92%
“…It has been reported that obesity is involved in the onset of CAD 27,28 and in the present study BMI was found to be significantly higher in the recurrence group, which is consistent with the recently proposed concept of metabolic syndrome in which abdominal obesity is an important risk factor for cardiovascular disease.…”
Section: Relationships Between Risk Factors and Recurrence Of Ischemisupporting
confidence: 92%
“…In adults, an elevated BMI is associated with increased rates of diabetes mellitus, heart disease, cancer and death. [60][61][62] Similarly, elevated BMI in children is associated with increased blood pressure, hyperlipidemia and type 2 diabetes, as well as development of coronary artery disease and increased all-cause mortality later in life. 1,[63][64][65][66] Children with elevated BMI are at high risk of having elevated BMI as adults.…”
Section: Limitationsmentioning
confidence: 99%
“…Similarly, a recent study by Michos et al 4 demonstrated that a familial propensity to subclinical atherosclerosis interacts with metabolic risk factors, magnifying the risk of individuals exposed multiple risk factors. In addition, a family study by Mora et al 5 suggested that obesity may substantially increase the risk of CHD for siblings of probands with premature CHD. These observations suggest that the additional risk associated with family history may in part be attributable to increased arterial vulnerability to the proatherogenic effects of metabolic risk factors.…”
Section: Juonala Et Almentioning
confidence: 99%
“…Michos et al 4 observed that subjects with a family history of CHD had higher prevalence of coronary artery calcium in the presence of metabolic risk factors than those without family history. Mora et al 5 reported that obesity substantially increased the risk of CHD for siblings of subjects with premature CHD, especially for those with clustering of risk markers.…”
mentioning
confidence: 99%